Attitudes Toward Cannabis Use During Labor in the United States - Brooke A. Chernek; Kara R. Skelton (Mary Ann Liebert, 2022)
Objective: Little is known about women's attitudes toward cannabis use during labor. We aim to address this gap by (1) reporting on attitudes toward cannabis use during labor, including cannabis use during most recent childbirth; and (2) examining the extent to which attitudes, willingness to use cannabis during labor, and cannabis use during most recent childbirth vary across state-level cannabis policies. Methods: In Spring 2021, we recruited biological women of reproductive age (18?40 years) for an online survey. We collected sociodemographic information and asked women about their attitudes toward cannabis use during labor, willingness to use cannabis during labor, and prior cannabis use during most recent childbirth. We ran descriptive statistics and used Fisher's exact tests to examine the association between state cannabis policies and attitudes toward cannabis use during labor, including willingness to use cannabis during labor. Results: In our sample (N?=?163), most women reported they would either consider using (47.85%) or previously used (3.07%) cannabis during labor. Compared with women who would not use, women who reported willingness to use or prior use of cannabis during labor were more likely to report a lower annual household income (p?=?0.001) and education level (p?<?0.001). Women willing to consider cannabis use were also more likely to report prenatal cannabis use (p?<?0.001) and reside in a state with recreational cannabis legalization (p?=?0.003). Women who would not consider using cannabis during labor were more likely to perceive one or more risks of use compared with women who would consider using cannabis during labor (90.00% vs. 72.29%, respectively; p?=?0.005). In fully illegal states, 66% of women reported they would be more likely to use cannabis during labor if it were legal. Conclusions: Future research is urgently needed to guide clinical practice. To mitigate adverse health outcomes, prenatal care providers should discuss cannabis use during labor with their patients.